Characterization of the Stimulation of Ethylene Production by Galactose in Tomato (Lycopersicon esculentum Mill.) Fruit - Kim, Jongkee (1987)
We have characterized the stimulation of ethylene production by galactose in tomatoes (Lycopersicon esculentum Mill.). The effect of concentration was studied by infiltrating 0, 4, 40, 100, 200, 400, or 800 micrograms galactose for each gram of fresh fruit weight into mature green `Rutgers' fruit. Both 400 and 800 micrograms per gram fresh weight consistently stimulated a transient increase in ethylene approximately 25 hours after infiltration; the lower concentrations did not. Carbon dioxide evolution of fruit infiltrated with 400 to 800 micrograms per gram fresh weight was greater than that of lower concentrations. The ripening mutants, rin and nor, also showed the transient increase in ethylene and elevated CO(2) evolution by 400 micrograms per gram fresh weight galactose. 1-Aminocyclopropane-1-carboxylic acid (ACC) content and ACC-synthase activity increased concurrently with ethylene production. However, galactose did not stimulate ACC-synthase activity in vitro. The infiltrated galactose in pericarp tissue was rapidly metabolized, decreasing to endogenous levels within 50 hours. Infiltrated galacturonic acid, dulcitol, and mannose stimulated transient increases in ethylene production similar to that of galactose. The following sugars produced no response: sucrose, fructose, glucose, rhamnose, arabinose, xylose, raffinose, lactose, and sorbitol.